An atypical case of HLA-B27-associated uveitis with hypopyon and posterior segment involvement - Xie, Thomas; Bitton, Etty (Canadian Journal of Optometry, 2012)
The presence of a hypopyon and posterior segment involvement are uncommon clinical findings in HLA-B27-associated uveitis. Furthermore, first-time attacks rarely occur in the elderly. This report highlights an atypical uveitis case involving an older patient, an evident hypopyon and severe intermediate uveitis in one eye. The 60-year-old Caucasian male was admitted for a painful, red eye with a sudden decreased vision to hand motion, in the affected eye. Ocular and systemic history were unremarkable. An anterior chamber examination of the eye revealed extensive cells and flare with a conspicuous hypopyon. An evaluation of the posterior segment revealed significant vitreous haze, obstructing all view to the retina. Despite the age and the atypical ocular findings of the patient, a diagnosis of HLA-B27-associated uveitis was made following an extensive clinical and laboratory evaluation. The inflammatory condition was successfully managed with a combination of intravenous, topical and oral corticosteroids tapered over the course of a few weeks, and visual acuity recovered to 20/30. This case is an important reminder that atypical signs, such as a hypopyon or intermediate uveitis, can occur and may be a significant sign of HLA-B27-associated uveitis. Clinicians should be aware of the diverse manifestations of HLA-B27-associated uveitis and be careful to include a comprehensive assessment of both the anterior and posterior segments of any presenting painful, red eye.